Causal links between circulatory inflammatory cytokines and risk of digestive polyps: a Mendelian randomization analysis - Yan, Ziqi; Zheng, Hongming; Feng, Jieni; Li, Yiting; Hu, Zhifan; Wu, Yuan; Liao, Guibin; Miao, Taosheng; Qiu, Zexin; Mo, Qiaolan; Li, Jia; Lai, Ailin; et al. (Frontiers in Pharmacology, 2024)
Background There is a high morbidity of polyps in the digestive tract, and certain subtypes of polyps are thought to induce cancer progression and often recur, which may be associated with chronic inflammation. Mendelian randomization (MR) can help identify potential causative relationships and inform early treatment action. Methods We performed a bidirectional two-sample MR analysis implementing the results from genome-wide association studies for 41 serum cytokines from 8,293 Finnish individuals, and three types of polyps from European ancestry, respectively, including gastric polyp (6,155 cases vs. 341,871 controls), colonic polyp (22,049 cases vs. 332,368 controls) and gallbladder polyp (458 cases vs. 340,083 controls). Inverse-variance weighted (IVW), weight median (WM), and MR-Egger methods were used for calculating causal estimates. Furthermore, Bayesian model averaging MR (MR-BMA) method was employed to detect the dominant causal circulatory cytokines with adjustment for pleiotropy effects. Results Our univariable MR using inverse-variance weight method identified causal associations of IL-2ra (OR: 0.892, 95%CI: 0.828–0.961, p = 0.003), MIG (OR: 1.124, 95%CI: 1.046–1.207, p = 0.001) and IL-18 (OR: 0.912, 95%CI: 0.852–0.977, p = 0.008) with gastric polyp, MIP1b (OR: 0.956, 95%CI: 0.927–0.987, p = 0.005) and IL-6 (OR: 0.931, 95%CI: 0.870–0.995, p = 0.035) with colonic polyp and IL-9 (OR: 0.523, 95%CI: 0.345–0.794, p = 0.0007) with gallbladder polyp. Finally, our MR-BMA analysis prioritized MIG (MIP = 0.332, MACE = 0.022; PP: 0.264, MSCE = 0.059), IL-18 (MIP = 0.302, MACE = −0.020; PP: 0.243, MSCE = −0.059) and IL-2ra (MIP: 0.129; MACE: −0.005; PP: 0.112, MSCE: −0.031) for gastric polyp, and MIP1b (MIP = 0.752, MACE = −0.033; PP: 0.665, MSCE = −0.044) and IL-6 (MIP: 0.196; MACE: −0.012; PP: 0.140, MSCE: −0.064) for colonic polyp, and IL-9 (MIP = 0.936, MACE = −0.446; PP: 0.781, MSCE = −0.478) for gallbladder polyp as the top-ranked protective factors. Conclusion Our research advances the current understanding of the function of certain inflammatory biomarker pathways in the genesis and malignant mutation of polyps in the digestive tract. Deeper substantiation is necessary to assess the potential of these cytokines as pharmacological or lifestyle targets for digestive polyps prevention.